Samarbeidets vilkår etter Samhandlingsreformen - en enkeltcase-studie - Løken, Therese Dwyer; Kirchhoff, Jörg W. (Nordisk tidsskrift for helseforskning, 2018)
The home nursing care is responsible for providing health care to patients with chronic and complex disorders in the municipality. This requires interprofessional collaboration between the nurses and general practitioners (GP`s). This article explores how the Coordination Reform has affected the collaboration between GP`s and nurses in the home nursing care, and what organisational factors are important for the collaboration. The results are based on a case study with focus group interviews including 20 nurses and in depth interviews with four GP`s. Analysis revealed that the Coordination reform has led to an asymmetry in the need for collaboration where the nurses have an increase in the need for collaboration. In addition, nurses wanted more meetings in patients` homes to discuss patients' health care needs. However, the funding system attached to the GP`s and their role as self-employed was an organisational barrier meeting nurses' needs.
Keywords: hjemmesykepleie; fastleger; Samhandlingsreformen; tverrprofesjonelt samarbeid; organisatoriske faktorer; home nursing care; general practitioners; the Coordination Reform; interprofessional collaboration; organisational factors